Medidas socioeducativas em meio aberto: Processo educativo para o adolescente autor de ato infracional? - Andrade, Vanessa Alves Trigueiro de (2015)
The infractional acts committed by adolescents are facts that, ever more, shocked the society and there are several reasons for which lead to such practices. Since the beginnings of the colonization of Brazil, in 1500, the attending policies to child and to the adolescent has embarked on several pathways as the repression, social control, stigmatization, the guarantee of rights. This last was achieved in 1988 with the Federal Constitution and regulated in 1990 with the Statute of Children and Adolescents through which was materialized the Doctrine of the Integral Protection. However, this policy is still poorly used, have not shown satisfactory results becoming the target of much criticism. In Article 112, the ECA, deals with socioeducational measures applied to the adolescent who commits an infractional act, which are intended to (re)imposition of the rights, the interruption of infractional trajectory and social inclusion, educational, cultural and professional of these subjects thus aiming the full exercise of citizenship thereof. This study aims to analyze the effectiveness of measures socioeducational taken to comply in an open environment on adolescent social-educational process in conflict with the law, considering the Brazilian and Paraiba scenario with regard to issue. In the first part of the study detailing the historical trajectory of the child care policy and adolescents in Brazil. Thereafter, we will treat of the attending policies to the adolescents in conflict with the law, the infractional act, the socioeducational measures in general, the National Socio-Educational Services System. And finally, we discuss the central theme of our study when then identify characteristics of Socio-Educational System in Half Open. We will highlight the issue of dichotomy between the theoretical literature on the children and adolescents and the care provided to these social actors, as well as the need for educational measures be undertaken in coordination with the Rights Assurance System in order to fully achieve the objectives which are proposed. For the elaboration of this dissertation, we conducted a bibliographic and documentary research and although we have presented some quantitative data, the analysis of the research happened in a predominantly qualitative way based on the analytical critical method.